Hypoxic ucMSC-secreted exosomal miR-125b promotes endothelial cell survival and migration during wound healing by targeting TP53INP1 - Xiao-Fei Zhang; Ting Wang; Zi-Xuan Wang; Kun-Peng Huang; Yun-Wei Zhang; Guo-Liang Wang; Hong-Ji Zhang; Zi-Han Chen; Chang-Yan Wang; Jin-Xiang Zhang; Hui Wang (Elsevier, 2021)
A hypoxic microenvironment is a common feature of skin wounds. Our previous study demonstrated that three-dimensional coculture of umbilical cord-derived mesenchymal stem cells (ucMSCs) and endothelial cells facilitates cell communication and host integration in skin tissue engineering. Here, we aimed to identify the mechanism by which ucMSCs affect endothelial cells under hypoxic conditions after skin injury. We demonstrate that hypoxia enhances the exosome-mediated paracrine function of ucMSCs, which increases endothelial cell proliferation and migration. In a mouse full-thickness skin injury model, ucMSC-derived exosomes can be taken up by endothelial cells and accelerate wound healing. Hypoxic exosomes lead to a better outcome than normoxic exosomes by promoting proliferation and inhibiting apoptosis. Mechanistically, microRNA-125b (miR-125b) transcription is induced by hypoxia in ucMSCs. After being packaged into hypoxic exosomes and transported to endothelial cells, miR-125b targets and suppresses the expression of tumor protein p53 inducible nuclear protein 1 (TP53INP1) and alleviates hypoxia-induced cell apoptosis. Inhibition of miR-125b-TP53INP1 interaction attenuates the protective effect of hypoxic exosomes. Moreover, artificial agomiR-125b can accelerate wound healing in vivo. Our findings reveal communication between ucMSCs and endothelial cells via exosomal miR-125b/TP53INP1 signaling in the hypoxic microenvironment and present hypoxic exosomes as a promising therapeutic strategy to enhance cutaneous repair.